Katalog : Gemälde des 20.Jahrhunderts. - Staatliche Museen zu Berlin, Nationalgalerie, Berlin (Berlin : Akademie-Verlag, 1976)
Ahlers-Hestermann, Friedrich ; Archipow, Abram Jefimowitsch ; Bartning, Ludwig ; Baumeister, Willi ; Bergander, Rudolf ; Beyer, Tom ; Birkle, Albert ; Böttcher, Manfred ; Brendel, Günther ; Bruse, Hermann ; Büttner, Erich ; etc.
Katalog : Gemälde des 20.Jahrhunderts, Staatliche Museen zu Berlin, 1977
boek